Lisbon-Oporto rivalry in the 19th and 20th centuries - Mata, Maria Eugénia (2020)
As pointed out in previous chapters, Lisbon and Oporto have been, since the 18th century, the two main Portuguese urban centres, forming a class of their own, clearly different from any other Portuguese town. This has thrust the two communities into a rivalry which has left its imprint on almost every aspect of Portuguese social life.